2002
DOI: 10.1007/s00709-002-0027-6
|View full text |Cite
|
Sign up to set email alerts
|

The Commelina yellow mottle virus promoter drives companion-cell-specific gene expression in multiple organs of transgenic tobacco

Abstract: Previous work has demonstrated that some endogenous plant gene promoters are active in selective companion cells of the phloem, depending on organ types and developmental stages. Here we report that the Commelina yellow mottle virus (CoYMV) promoter is active in the companion cells of leaves, stems and roots of transgenic Nicotiana tabacum cv. Xanthi NN, using beta-glucuronidase (GUS) as a reporter. Thus, the CoYMV promoter has a broad organ specificity. This promoter can be useful in molecular studies on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…CoYMVp is known to confer strong companion cellspecific expression (Medberry et al, 1992;Matsuda et al, 2002). A construct in which CoYMVp was fused to AtSUC2 complementary DNA (cDNA) was shown to rescue the Atsuc2-4 -/-knockout mutation (Srivastava et al, 2009b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CoYMVp is known to confer strong companion cellspecific expression (Medberry et al, 1992;Matsuda et al, 2002). A construct in which CoYMVp was fused to AtSUC2 complementary DNA (cDNA) was shown to rescue the Atsuc2-4 -/-knockout mutation (Srivastava et al, 2009b).…”
Section: Resultsmentioning
confidence: 99%
“…It was predicted that although these promoters had similar spatial expression as the natural AtSUC2p, differences in responses to stimuli could be used to maintain high levels of SUT expression and, consequently, high levels of phloem transport in conditions where transport may normally be down-regulated (Srivastava et al, 2009b). CoYMVp is from Commelina yellow mottle virus, but despite its viral origin, it is specific to phloem companion cells (Medberry et al, 1992;Matsuda et al, 2002). Research presented here demonstrates that while AtSUC2p is repressed, CoYMVp is up-regulated in the presence of elevated Suc levels and thus can be used to bypass possible endogenous regulation of AtSUC2 expression at the transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we generated transgenic tobacco expressing the 3a MP of Cucumber mosaic virus (CMV) fused to green fluorescent protein (GFP) under the control of the CC-specific promoter of Commelina yellow mottle virus (CoYMV) (Matsuda et al, 2002). We found that, in the absence of viral replication, the fusion protein trafficked from CC to SE and further from the "symplasmically isolated" SE-CC complex into neighboring cells.…”
Section: Introductionmentioning
confidence: 99%
“…4A). The pCoYMV promoter is from Commelina Yellow Mottle Virus and known to confer strong companion cell-specific expression (Medberry et al, 1992;Matsuda et al, 2002). It is also up-regulated by Suc, whereas another companion cell-specific promoter, Arabidopsis SUCROSE-PROTON SYMPORTER2 (pAtSUC2), is repressed by Suc (Dasgupta et al, 2014).…”
mentioning
confidence: 99%